Synaptic proteins and receptors defects in autism spectrum disorders - Chen, Jianling; Yu, Shunying; Fu, Yingmei; Li, Xiaohong (Frontiers in Cellular Neuroscience, 2014)
Recent studies have found that hundreds of genetic variants, including common and rare variants, rare and de novo mutations, and common polymorphisms have contributed to the occurrence of autism spectrum disorders (ASDs). The mutations in a number of genes such as neurexin, neuroligin, postsynaptic density protein 95 (PSD-95), SH3 and multiple ankyrin repeat domains 3 (SHANK3), synapsin, gephyrin, cadherin (CDH) and protocadherin (PCDH), thousand-and-one-amino acid 2 kinase (TAOK2), and contactin (CNTN), have been shown to play important roles in the development and function of synapses. In addition, synaptic receptors, such as gamma-aminobutyric acid (GABA) receptors and glutamate receptors, have also been associated with ASDs. This review will primarily focus on the defects of synaptic proteins and receptors associated with ASDs and their roles in the pathogenesis of ASDs via synaptic pathways.